Relatório do estágio curricular supervisionado em medicina veterinária área de concentração: avicultura – matrizes e incubatório - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The supervised curricular internship in Veterinary Medicine was carried out in a agroindustry in the western region of Santa Catarina, specifically in the city of Chapecó, focused on the poultry sector. The internship aimed to monitor the processes developed in the company's rearing, matrices and hatchery, during the period from September 8th to January 5th, developing a workload of 455 hours, under the supervision of Veterinarian Paulo Cenci. During this time it was The internship was carried out in the company's own breeding unit, production of integrated and hatchery. It was possible to follow the selection activities, a very important in rearing, vaccines, feeding, health monitoring, arrival of eggs for incubation and monitoring of hatchery activities, where the main were selection of viable eggs, storage, preheating, incubation, management of chicks and shipping.
Curricular internship report supervised in veterinary medicine concentration area: poultry farming – parents and hatchery
Keywords: Biosseguridade; Genética; Matrices; Biosecurity; Genetics; Matrizes; CNPQ::CIENCIAS AGRARIAS